2013
DOI: 10.1186/2051-5960-1-46
|View full text |Cite
|
Sign up to set email alerts
|

CSF Presenilin-1 complexes are increased in Alzheimer’s disease

Abstract: BackgroundPresenilin-1 (PS1) is the active component of the amyloid precursor protein cleaving γ-secretase complex. PS1 protein is a transmembrane protein containing multiple hydrophobic regions which presence in cerebrospinal fluid (CSF) has not been measured to date. This study assesses whether PS1 and other components of the γ-secretase complex are present in CSF.ResultsHere, we show that PS1 is present in ventricular post-mortem and lumbar ante-mortem CSF, and plasma as 100–150-kDa hetero-complexes contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 55 publications
1
28
0
1
Order By: Relevance
“…We did not provide direct evidence that exogenous apoE or apoJ directly bound to CSF A β 42 to enhance its solubility, even though apolipoproteins are known to interact with A β and may prevent its aggregation 22 , 33 , 36 , 37 We also did not use gamma-secretase inhibitors to account for de novo production of A β 42 peptides, but gamma-secretase activity has not been reported in CSF and presenilin 1 and 2 fragments detected in CSF are felt to represent nonspecific aggregation rather than gamma-secretase complexes. 38 We propose that alterations in CSF % susA β are due to technical and biological factors, and susA β 42 levels, t-Tau/susA β 42 ratio, as well as their impact on other biological correlates of AD should be interpreted with care because these in vitro measures reflect amyloid protein's total abundance as well as its dynamic interactions with other AD-associated proteins and AD itself.…”
Section: Discussionmentioning
confidence: 99%
“…We did not provide direct evidence that exogenous apoE or apoJ directly bound to CSF A β 42 to enhance its solubility, even though apolipoproteins are known to interact with A β and may prevent its aggregation 22 , 33 , 36 , 37 We also did not use gamma-secretase inhibitors to account for de novo production of A β 42 peptides, but gamma-secretase activity has not been reported in CSF and presenilin 1 and 2 fragments detected in CSF are felt to represent nonspecific aggregation rather than gamma-secretase complexes. 38 We propose that alterations in CSF % susA β are due to technical and biological factors, and susA β 42 levels, t-Tau/susA β 42 ratio, as well as their impact on other biological correlates of AD should be interpreted with care because these in vitro measures reflect amyloid protein's total abundance as well as its dynamic interactions with other AD-associated proteins and AD itself.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of blots with antibodies for the different γ-secretase subunits confirmed that APH1 and PEN2, but not nicastrin, are present in CSF as complexes (see Ref. ( 25 ) to complete information). In all analyses performed on PS1, denaturation before electrophoresis was conducted at 50°C.…”
Section: Soluble Full-length and Heteromers Of Sapp In Csfmentioning
confidence: 77%
“…Accordingly, it has been assumed that the BACE1 present in CSF is a truncated soluble form of the originally membrane-bound BACE1 missing the transmembrane and intracellular domains ( 37 ). Indeed, some studies failed to demonstrate the presence of BACE1 containing the C-terminal domain in human CSF and plasma ( 38 , 39 ), but others detected immunoreactivity with BACE1 C-terminal antibodies ( 25 , 31 , 33 ), suggesting that full-length BACE1 exists in this fluid. The presence of full-length BACE1, together with its truncated form, has also been demonstrated in conditioned media from cultured neurons ( 40 ).…”
Section: β-Secretase and Tace/α-secretase Activities In Csfmentioning
confidence: 99%
“…A mechanism for sAPPf to appear in CSF has yet to be determined, but passive release from brain cells or neuronal cell death may be possible, as recently observed for BACE1 [ 21 ]. Full-length BACE1 and other membrane resident protein, such as presenilin-1, are present in CSF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%